PERAN PENYULUH PERIKANAN TERHADAP PELAKU USAHA DALAM PEMBENTUKAN KELOMPOK PERIKANAN DI KOTA LUBUKLINGGAU - Widariani; Lis M Yapanto; Heri Wahyudi (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
Abstract: This study aims to analyze the role of fisheries extension workers to business actors in the formation of fisheries groups in Lubuklinggau City. The research method uses a quantitative approach with a Likert scale questionnaire instrument which was distributed to 30 respondents of fisheries business actors. The data was analyzed descriptively to determine the level of role of fisheries extension workers which included four indicators (facilitators, motivators, communicators, and mentors) and the level of fisheries group formation which included three aspects (institutional, administrative and legality, as well as benefits and sustainability). The results of the study show that the role of fisheries extension workers is in a very high category with a total score of 2,913 out of a maximum score of 3,150. The formation of fisheries groups is also in the high category with a total score of 1,295 out of a maximum score of 1,800. There is a positive relationship between the role of fisheries extension workers and the formation of fisheries groups. This study recommends increasing the intensity of mentoring and strengthening the administrative aspects of the group to support the sustainability of fisheries groups in Lubuklinggau City.   Keywords: The Role of Extension Workers, Fisheries Groups, Business Actors, Lubuklinggau   Abstrak: Penelitian ini bertujuan untuk menganalisis peran penyuluh perikanan terhadap pelaku usaha dalam pembentukan kelompok perikanan di Kota Lubuklinggau. Metode penelitian menggunakan pendekatan kuantitatif dengan instrumen kuesioner skala Likert yang didistribusikan kepada 30 responden pelaku usaha perikanan. Data dianalisis secara deskriptif untuk mengetahui tingkat peran penyuluh perikanan yang meliputi empat indikator (fasilitator, motivator, komunikator, dan mentor) dan tingkat pembentukan kelompok perikanan yang mencakup tiga aspek (kelembagaan, administrasi dan legalitas, serta manfaat dan keberlanjutan). Hasil penelitian menunjukkan bahwa peran penyuluh perikanan berada dalam kategori yang sangat tinggi dengan total skor 2.913 dari skor maksimal 3.150. Pembentukan kelompok perikanan juga masuk kategori tinggi dengan total skor 1.295 dari skor maksimal 1.800. Ada hubungan positif antara peran penyuluh perikanan dengan pembentukan kelompok perikanan. Penelitian ini merekomendasikan peningkatan intensitas pendampingan dan penguatan aspek administrasi kelompok untuk mendukung keberlanjutan kelompok perikanan di Kota Lubuklinggau.   Kata Kunci: Peran Penyuluh, Kelompok Perikanan, Pelaku Usaha, Lubuklinggau